2005
DOI: 10.1017/s0950268805004012
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal household study of Streptococcus pneumoniae nasopharyngeal carriage in a UK setting

Abstract: SUMMARYA 10-month longitudinal household study of pre-school children and their families was undertaken with monthly visits collecting epidemiological data and nasopharyngeal swabs in Hertfordshire, England from 2001 to 2002. Pneumococcal culture was with standard methods. In total, 121 families (489 individuals) took part. Mean prevalence of carriage ranged from 52 % for age groups 0-2 years, 45 % for 3-4 years, 21 % for 5-17 years and 8 % for o18 years. Carriage occurred more than once in 86 % of children ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
163
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(178 citation statements)
references
References 31 publications
13
163
0
2
Order By: Relevance
“…The higher incidences seen in the 1996-1997 and 1999-2000 seasons might have been related to the peaks of influenza seen in those seasons [21]. A recent study by Hussain et al showed that there were no significant seasonal differences in the prevalence of carriage of S. pneumoniae [22].…”
Section: Discussionmentioning
confidence: 96%
“…The higher incidences seen in the 1996-1997 and 1999-2000 seasons might have been related to the peaks of influenza seen in those seasons [21]. A recent study by Hussain et al showed that there were no significant seasonal differences in the prevalence of carriage of S. pneumoniae [22].…”
Section: Discussionmentioning
confidence: 96%
“…Children are the main source of pneumococcal infection for older people, because children are much more frequently nasopharyngeal carriers of percentile of the GMC ratios; the horizontal line within the box is the median ratio. A ratio of >1 means that the GMC was higher at the same point in time after the 2nd dose than after the 1st dose pneumococci than are older adults [113]. 2.…”
Section: Model Structurementioning
confidence: 99%
“…3). The levels of SSURE [1][2][3][4][5] and SSURE 2ϩ3 binding to immobilized hTSP-1 were comparable when used in similar molecular ratios (related to immobilized hTSP-1). In contrast, the SSURE 2 protein, representing a single repeat of PavB, showed a very low level of hTSP-1 binding (Fig.…”
Section: Repeating Structures Of Pavb and Pspc Are Involved In Thementioning
confidence: 99%
“…Similar to the ELISA approach, all PavB-SSURE-proteins bound dosedependently to immobilized hTSP-1 in a micromolar range. The association of SSURE [1][2][3][4][5] and SSURE 2 to hTSP-1 was comparable; however, a 5-fold higher concentration of SSURE 2ϩ3 had to be used to reach a similar level of binding as measured for Proteins were detected using a specific polyclonal mouse anti-SSURE 2ϩ3 antibody or a monoclonal mouse anti-penta-His antibody and an alkaline phosphatase-coupled secondary anti-mouse antibody. D, SDS-PAGE of heterologously expressed PspC2 (SH2, SH3, SM1) and PspC3 (SH13) fragments stained with CBB R250 and corresponding immunoblots.…”
Section: Kinetics Of Pavb and Pspc Binding To Htsp-1 As Analyzed By Smentioning
confidence: 99%
See 1 more Smart Citation